Indeks Penulis Volume 29, Tahun 2009 - Indeks Penulis Volume 29, Tahun 2009 (agriTECH, 2009)
Ainuri, M. 208Antara, N.S. 1Apituley, D.A.N. 22Aryanta, W.R. 1Aspiyanto. 108Astuti, M. 59Bachruddin, Z. 53Banyuaji, A. 171Budiharti, U. 42Cahyanto, M.N. 53Christian, A.E. 71Dibia, I.N. 1Dwiyanti, H. 16Goenadi, S. 188Hadi, P. 188Hariadi, M. 219Harimurti, S. 142Harmayani, E. 96Haryadi. 87Hastuti, P. 147Herawati, H. 47Heru Joko. 198Hidayat, C. 122